2020
DOI: 10.1080/01457632.2019.1707390
|View full text |Cite
|
Sign up to set email alerts
|

Flow Boiling of Water in a Rectangular Metallic Microchannel

Abstract: The article presents the experimental results of flow boiling of water in single rectangular microchannels. Three rectangular copper microchannels having the same hydraulic diameter (0.56 mm) and length (62 mm) but different aspect ratios (width/height, 0.5, 2.56, and 4.94) were investigated using de-ionized water as the working fluid. The experiments were conducted over the experimental range of mass flux 200-800 kg/(m 2 s), heat flux 4-1350 kW/m 2 and inlet subcooling of $14 K. The results showed that the ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 45 publications
(26 citation statements)
references
References 51 publications
(95 reference statements)
1
13
0
Order By: Relevance
“…They concluded that the heat transfer coefficient increases with increasing aspect ratio up to AR= 3.54 and then decreases. Özdemir et al [107] studied flow boiling of water in single copper channels of hydraulic diameter 0.56 mm, length 62 mm and AR = 0.5, 2.56 and 4.99. The authors reported that the heat transfer coefficient increased as the aspect ratio decreased up to a heat flux of approximately 500 kW/m 2 .…”
Section: Effect Of Channel Aspect Ratiomentioning
confidence: 99%
“…They concluded that the heat transfer coefficient increases with increasing aspect ratio up to AR= 3.54 and then decreases. Özdemir et al [107] studied flow boiling of water in single copper channels of hydraulic diameter 0.56 mm, length 62 mm and AR = 0.5, 2.56 and 4.99. The authors reported that the heat transfer coefficient increased as the aspect ratio decreased up to a heat flux of approximately 500 kW/m 2 .…”
Section: Effect Of Channel Aspect Ratiomentioning
confidence: 99%
“…The experimental data utilised in this study are obtained from Özdemir's [18] experimental test setup. The data are procured from the voltage, current, mass flow rate, pressure measurements and thermocouple readings.…”
Section: Data Reductionmentioning
confidence: 99%
“…The local axial wall temperatures were measured in the 0.6 mm inner diameter and 6 mm length holes at the side of each microchannel test section. The holes were located 1.1 mm distance below the channel bottom to accommodate K-type thermocouples [18]. Relevant properties and their equations are given as follows.…”
Section: Data Reductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kim and Sohn [10] developed a correlation for heat transfer coefficient after an experimental study of the flow boiling in a rectangular channel with large range of Reynolds number and heat flux. Özdemir et al [11] studied experimentally the flow boiling of water in single rectangular microchannels.…”
Section: Introductionmentioning
confidence: 99%